Design rewiring using ATPG. - Veneris, A. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Logic optimization is the step of the very large scale integration (VLSI) design cycle where the designer performs modifications on a design to satisfy different constraints such as area, power, or delay. Recently, automated test pattern generation (ATPG)-based design rewiring techniques for technology-dependent logic optimization have gained increasing popularity. In this paper, the authors propose a new operational framework to design rewiring that uses ATPG and diagnosis algorithms. They also examine its complexity requirements and discuss different implementation tradeoffs. To perform this study, the authors reduce the problem of design rewiring to the process of injecting a redundant set of multiple pattern faults. This formulation arrives at a new set of results with theoretical and practical applications. Experiments demonstrate the competitiveness of the approach and motivate future work in the area.